EXPERIMENTAL INVESTIGATION ON ELECTRICAL LOAD CHARACTERISTICS OF A MONOCRYSTALLINE PHOTOVOLTAIC PANEL UNDER RGB-FILTERED BROADBAND LED ILLUMINATION - M. Raynaldo Sandita Powa; Afrizal Mayub; Euis Nursaadah (Indonesian Physical Review, 2026)
RGB-filtered broadband illumination was applied to a monocrystalline photovoltaic (PV) panel under controlled indoor conditions to observe its electrical load characteristics. Optical red, green, and blue filters are used to produce RGB channel dominance in the transmitted light from a 5000 K LED source, without implying narrowband spectral separation. Sequential resistive loads (10 steps from 100 Ω to 4700 Ω) are applied to generate voltage–current operating points that reconstruct I–V and P–V characteristics under each filtering condition. Standard PV parameters, including estimated short-circuit current (Isc), open-circuit voltage (Voc), maximum power point (MPP), and estimated fill factor (FF), are derived from load-based curve extrapolation. Lux measurements are recorded alongside the electrical data to provide a comparison with photometric brightness. The results show a consistent ordering of electrical performance where green-filtered illumination produces higher current and power output than red and blue under the present experimental conditions. The maximum power under green filtering is approximately 54% higher than red and more than 400% higher than blue. However, since irradiance and spectral power distribution are not measured, differences in transmitted light intensity across filters may also contribute to the observed electrical variations, in addition to wavelength-related effects. The comparison using Isc/Lux and Pmax/Lux is presented only as an illustrative indicator and does not represent a physically rigorous photovoltaic performance metric. Therefore, the findings are interpreted as RGB-filtered broadband effects that are qualitatively consistent with known silicon spectral response behavior, rather than as direct spectral characterization. This work provides a practical, low-cost indoor protocol to observe photovoltaic response trends using accessible instrumentation without spectroradiometric equipment.